2019
DOI: 10.11650/tjm/181109
|View full text |Cite
|
Sign up to set email alerts
|

General Decay Rates for a Laminated Beam with Memory

Abstract: In previous work [23], Mustafa considered a viscoelastic laminated beam system with structural damping in the case of equal-speed wave propagations, and established explicit energy decay formula which gives the best decay rates. In this paper, we continue to consider the similar problems and establish the general decay result for the energy, to system with structural damping in the case of non-equal wave speeds and to system without structural damping in the case of equal wave speeds, respectively. For the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Mustafa [15, 16] extended the result to obtain two general decay results under the assumption of equation (4). Li et al [17] and Chen et al [18] extended the result to the case of non-equal speeds. Raposo et al [19] considered the following system:…”
Section: Introductionmentioning
confidence: 99%
“…Mustafa [15, 16] extended the result to obtain two general decay results under the assumption of equation (4). Li et al [17] and Chen et al [18] extended the result to the case of non-equal speeds. Raposo et al [19] considered the following system:…”
Section: Introductionmentioning
confidence: 99%
“…Complexity us, B is coercive on V × V. Consequently, using Lax-Milgram theorem, we conclude that (30) has a unique solution: 5 , and v 8 into (24)- (26) and 28, respectively, we have…”
Section: Well Posednessmentioning
confidence: 75%
“…By adding suitable damping effects, such as internal damping, (boundary) frictional damping, and viscoelastic damping, it was shown that if the linear damping terms are added in two of the three equations, system (4) is exponentially stable under the "equal wave speeds" assumption (ρ/I ρ ) � (G/D). But if the damping terms are added in the three equations, then the system decays exponentially without the equal wave speeds assumption, see, for example, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For thermoelastic laminated Timoshenko beam, there are few published works, we can mention the results due to Liu and Zhao [18] and Apalara [19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we referred to [11,14,15] for the decay estimate of degenerate wave equations with localized damping and viscoelastic damping, and system of linear equations with boundary memory dissipations. The general decay of a thermoelastic laminated beam with past history was researched in [16,30] and the general and optimal decay result for a Moore-Gibson-Thompson equation with memory was established in [28].…”
Section: Zhiqing Liu and Zhong Bo Fangmentioning
confidence: 99%